The Peer Education Approach in Adolescents- Narrative Review Article. - Fatemeh Abdi; Masoumeh Simbar (Tehran University of Medical Sciences, 2013)
Adolescence is an important stage of human life span, which crucial developmental processes occur. Since peers play a critical role in the psychosocial development of most adolescents, peer education is currently considered as a health promotion strategy in adolescents. Peer education is defined as a system of delivering knowledge that improves social learning and provides psychosocial support. As identifying the outcomes of different educational approaches will be beneficial in choosing the most effective programs for training adolescents, the present article reviewed the impact of the peer education approach on adolescents. In this review, databases such as PubMed, EMBASE, ISI, and Iranian databases, from 1999 to 2013, were searched using a number of keywords. Peer education is an effective tool for promoting healthy behaviors among adolescents. The development of this social process depends on the settings, context, and the values and expectations of the participants. Therefore, designing such programs requires proper preparation, training, supervision, and evaluation.